Mulher, trabalho e maternidade: uma visão contemporânea - Maluf, Vera Maria Daher (2009)
The study examined the relationships of women executives with high professional achievement, who are also mothers. It is qualitative-quantitative research conducted via the Internet with 45 women executives from various service companies. For data collection we used the following instruments: Social Perception Questionnaire, which consists of five parts that measure Gender Differences, Motherhood, Occupation, Emotional Relationships; Contemporary View, Brazilian Version of the Quality of Life Questionaire - SF 36 and Sociodemographic Questionnaire. The results showed that, for the women surveyed, it is in part a time of growth, and in part a time of conflict. The study's finding that the women surveyed manage the quality of life by providing opportunities contradicts much of the previous literature. Until now, it was believed that the quality of life for such women, who work 10 to 14 hours a day, is greatly compromised. The study does not support this conclusion. The fact that these women are in positions of extreme complexity is not seen as burdensome, but instead stimulating. Despite the belief that motherhood is the paramount value to women, the women surveyed do not behave and / or made choices guided primarily by motherhood. They stated that in order to have children, financial conditions are necessary and also a companion who wants children. They also reported that the quest for professional achievement helped to foster more egalitarian relationships promoting personal and professional satisfaction. In conclusion, living in a historic moment, full of complexity and contradiction, the women surveyed are torn between the desire to assert themselves as actors who construct history with men, and the desire for motherhood and their role in monitoring the development of children. The place of these women in history remains both professional, economic, political, social, and intensely personal as well with respect to their role as mothers